Sensitivity and specificity of cone beam computed tomography in thin bony structures in maxillofacial surgery – A clinical trial. Issue 7 (September 2015) - Thönissen, P.; Ermer, M.A.; Schmelzeisen, R.; Gutwald, R.; Metzger, M.C.; Bittermann, G.
Abstract Introduction Cone-Beam Computed Tomography (CBCT) has become widely used in dentistry and maxillofacial surgery. Accuracy, sensitivity and specificity of thin bony structures below 0.5 mm have been subject of some in vitro studies. This prospective in vivo study investigates the correlation between preoperative CBCT-imaging and intraoperative clinical examination of thin bony structures. We hereby present results from daily clinical routine. Methods A total number of 80 sites in 64 patients has been examined to differentiate between preoperative 3D imaging and clinical measurements on cystic lesions in maxilla and mandible. Different CBCT-devices with a voxel size ranging from 0.08 mm to 0.4 mm were used. Results Overall-specificity found for detecting thin bony structures of the human jaw is 13.89%, overall sensitivity is 100%, positive predictive value (PPV) is 58.67% and negative predictive value (NPV) is 100%. Discussion Image quality is the key to make use of additional information CBCT provides and depends on spatial, temporal and contrast resolution. CBCT does not depict reliably thin bony structures of the jaw, even if high voxel resolution is used. Conclusion In selected cases using high resolution protocols should be considered despite affecting the patient with higher doses of radiation.